The significance of knowledge, skills, capabilities and competencies in fitness centers’ management - Mohd Firdaus Abdullah; Asiah Mohd Pilus; Nor Lailatul Azilah Hamdzah; Abu Yazid Abu Bakar; Mohamad Nizam Nazarudin (Allied Business Academies, 2021)
This study was conducted to determine the significance of knowledge, skills, capabilities and competencies in the management of fitness centres in Malaysia. From a broad perspective, this study is seen as significant to the development and growth of the fitness industry, especially in Malaysia, as well as to the agencies and departments involved in the policy formulation. For the purpose of collecting data, researchers have used quantitative methods by interviewing a total of 600 managers of fitness centres operating in the Federal Territory of Kuala Lumpur and Putrajaya and Selangor, the location of the focus of fitness centres. In general, the results of the study show that the majority of managers view the aspects of knowledge, skills, abilities and competencies as 'important' and 'very important' in ensuring the quality management of fitness service provider centres. It can be concluded that every fitness centre manager needs to have specific elements under the variables or components of knowledge, skills, abilities and competencies. Researchers are certain that this study has successfully led to some very crucial findings, which can benefit the development and advancement of the fitness services industry.